Donor-site morbidity after using bone autoplastic in reconstructive maxillofacial surgery. Meta-analysis. - Omelchenko, Artem; Kopchak, Andrey (The Ukrainian Scientific Medical Youth Journal, 2025)
the problem of donor-site diseases is an integral and important aspect of reconstructive surgical treatment using autografts. In maxillofacial surgery, autografts from the fibula and iliac crest are widely used to replace large defects of the lower and upper jaws. This approach to restoring lost bone structures is currently the “gold standard” due to the fact that bone autografts have the lowest risk of rejection compared to other options for bone grafting and provide the best anatomical and functional results in the long-term postoperative period. Donor site diseases are divided into early and late, they affect the quality of life of patients, limit their ability to work and sometimes require long-term rehabilitation. The aim of this study was to study the structure and conduct a comparative analysis of data (meta-analysis) on complications that occur in the area of ​​bone cortical-spongy autografts harvesting (donor-site diseases) from the iliac crest and fibular diaphysis in the treatment of patients with bone defects of the maxillofacial region. The meta-analysis used materials from the electronic databases PubMed, PubMed Central and Embase. Statistical analysis and calculations were performed in the IBM SPSS Statistics version 30.0.0.0(172) program. After processing 784 sources according to the PRISMA algorithm (Preferred Reporting Items for Systematic reviews and Meta-Analyses), the study included 16 scientific publications that contained information on the types of complications that occurred during bone tissue harvesting in the area of ​​the fibular diaphysis and iliac crest. According to the results of the meta-analysis, the fibular bone, as a donor site, is more dangerous in terms of the frequency of development of donor-site disease than the iliac crest according to such parameters as: infectious complications (p=0.04), gait disorders (p=0.04). The difference according to such a parameter as delayed healing is close to significant (p=0.05). The difference is not statistically significant according to such parameters as persistent pain syndrome (p=0.48), neurological disorders (sensitivity disorders) in the area of ​​donor bone harvesting (p=0.58) and the development of an aesthetic defect (p=0.12). Therefore, bone autoplastic, the source of which is the iliac crest, compared to the fibular shaft, is accompanied by a significantly lower risk of developing such donor-site disease as infectious complications and gait disorders. The difference in the development of complications such as delayed healing is close to significant.